2022
DOI: 10.1038/s41598-022-12583-w
|View full text |Cite
|
Sign up to set email alerts
|

Distinct clinicopathological and genomic features in solid and basaloid adenoid cystic carcinoma of the breast

Abstract: Adenoid cystic carcinoma (AdCC) of the breast is a rare indolent carcinoma of salivary gland-type tumors, frequently associated with MYB genetic alteration. Solid and basaloid adenoid cystic carcinoma (SB-AdCC) is considered a sparse variant of AdCC. This study sought to search for clinicopathological and genomic features in SB-AdCC. Registered clinicopathological data on a cohort of 13 AdCC of the breast cases, including six conventional adenoid cystic carcinoma (C-AdCC) cases and seven SB-AdCC cases, were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In studies analyzing only breast AdCC, the MYB IHC positivity ranges from 60% to 100%. 6,[11][12][13][14] Poling et al 14 found 100% (11/11) of breast AdCCs showed diffuse, moderate to strong MYB labeling, predominantly localized in the myoepithelial cell component. The authors compared this to other breast neoplasms and found only focal, weak expression in 63% (10/16) of TNBCs and 71% (5/7) of collagenous spherulosis cases, whereas no (0/5) cases of microglandular adenosis (MGA) were positive for MYB.…”
Section: Diagnostic Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…In studies analyzing only breast AdCC, the MYB IHC positivity ranges from 60% to 100%. 6,[11][12][13][14] Poling et al 14 found 100% (11/11) of breast AdCCs showed diffuse, moderate to strong MYB labeling, predominantly localized in the myoepithelial cell component. The authors compared this to other breast neoplasms and found only focal, weak expression in 63% (10/16) of TNBCs and 71% (5/7) of collagenous spherulosis cases, whereas no (0/5) cases of microglandular adenosis (MGA) were positive for MYB.…”
Section: Diagnostic Immunohistochemistrymentioning
confidence: 99%
“…It should be stated that although the MYB translocation can also be evaluated by fluorescence in situ hybridization (FISH), with detection rates ranging from 22.6% to 89%, the reported rate of MYB IHC expression is routinely higher than the detection of MYB rearrangement by FISH. 6,8,11,13,14 These findings should be unsurprising as the identification of multiple mechanisms leading to MYB overexpression limits the sensitivity of FISH testing. In addition, MYB rearrangement detected by FISH has been reported in 4% of non-AdCC breast neoplasms, both benign and malignant.…”
Section: Diagnostic Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer is the most common malignant tumor in women 1 ; there were approximately 2.3 million new breast cancer cases and 685,000 breast cancer deaths worldwide in 2020 2 . Of these cases, adenoid cystic carcinoma of the breast (BACC) accounts for less than 0.1% 3 . Most of these tumors exhibit indolent clinical behavior with a low tendency for axillary lymph node involvement and distant metastasis, showing significant differences from other pathologic types.…”
mentioning
confidence: 99%